Leveraging Ar-Rahnu micro financing for flood victims / Mohd Shafiz Saharan, Mohd Fazil Jamaludin and Khairul Azfar Adzahar - Saharan, Mohd Shafiz; Jamaludin, Mohd Fazil; Adzahar, Khairul Azfar (Faculty of Business and Management, Universiti Teknologi MARA Cawangan Kedah, 2022)
Malaysia was struck by a series of flash floods in December 2021, affecting numerous parts of the nation, including Kuala Lumpur, Selangor, Pahang, Kelantan, and Negeri Sembilan. These regions experienced increased rainfall, resulting in pluvial floods that caused significant property damage and fatalities. Despite a warning issued by the Malaysian Meteorological Department (MET Malaysia) on 17 December, 2021, victims and the government took little action to prepare for the inevitable. In addition, the department was accused of failing to issue a warning or update information to Malaysians on Typhoon Rai and Tropical Depression Twenty-Nine to Malaysians (“Malaysia’s Meteorological dept denies claims it failed to issue rainfall warnings”, 2021). At least 17 people perished as a result of the surge, and more than 60,000 people were evacuated to rescue centres (Farah Syazwani, 2021). Moreover, Malaysia was expected to have sustained damage of more than RM300 million consequent to the destruction of victims’ property and infrastructure in all affected states (Nurfarahin, 2021).